Burntcoat - Hall, Sarah 1974- (Faber & Faber, 2021)
In an unnamed British city, the virus is spreading, and like everyone else, the celebrated sculptor Edith Harkness retreats inside. She isolates herself in her immense studio, Burntcoat, with Halit, the lover she barely knows. As life outside changes irreparably, inside Burntcoat Edith and Halit find themselves changed as well: by the histories and responsibilities each carries and bears, by the fears and dangers of the world outside, and by the progressions of their new relationship. Author of "The Wolf Border.